INFLUENCIA DEL CAMPO GRAVITATORIO EXTERNO DEL UNIVERSO DE GÖDEL SOBRE EL ESPECTRO ENERGÉTICO DE PARTÍCULAS ESCALARES - Páuyac Huamán, Aníbal (2019)
In the external gravitational field of the Gödel universe with cylindrical symmetry, exact solutions of the scalar field equation and energy spectrum of the corresponding scalar particles are obtained. First, we considered the scalar particles only in an external gravitational field of the Gödel universe. Then, we considered the particles interacting with an external electromagnetic field, which is at the same time in the external gravitational field of the Gödel universe. The solution of the scalar field equation is obtained in the form of Jacobi polynomials. The energy spectrum of scalar particles proves to be discrete, due to rotation of the universe.